P260 The biological effect of tissue plasminogen (t-PA) activator and DNase intrapleural delivery in pleural infection patients. (December 2018) - Kanellakis, NI; Wrightson, JW; Hallifax, R; Mercer, R; Fayed, M; Asciak, R; Hedley, E; Dobson, M; Psallidas, I; Rahman, NM
Abstract : Background: Pleural infection (PI) is a major global disease with an increasing incidence. Pleural fluid (PF) drainage is essential for the successful treatment of PI. The MIST 2 study showed that the intrapleural administration of t-PA and DNase, or t-PA alone increases the volume of drained PF. A mouse study suggested that the volume increase is due to the interaction of the pleura with the t-PA via the MCP-1 pathway. Aim: To test the hypothesis that PF volume induction is mediated by the MCP-1 pathway. Methods: For the MIST 2 study 210 PI patients were randomised to receive for 3 days either: t-PA and DNase, t-PA and placebo, DNase and placebo or double placebo. Daily PF drainage was recorded and samples of PF were stored. PF MCP-1 levels were measured by ELISA. Results: During treatment (days 1–3) t-PA +DNase and t-PA +placebo significantly increased (ANOVA p<0.001) the volume of drained PF compared to DNase +placebo or double placebo groups. There was no significant difference (ANOVA p>0.05) between any of the groups during the post-treatment period (days 5–7). t-PA +DNase and t-PA groups triggered significantly higher (ANOVA p<0.001) PF volumes during treatment compared to post-treatment period. The intrapleural administration of t-PA increased the MCP-1 PF levels during treatment however no statistically significant difference was detected between patients who received t-PA and those who did not. MCP-1 expression was not correlated to the drug given nor the volume of drained PF. Conclusions: Intrapleural administration of t-PA (±DNase) stimulated a statistically significant rise of the volume of drained PF. The MCP-1 pathway did not correlate with PF volume output. We conclude that the PF increment seen with the administration of t-PA does not occur solely via activation of the MCP-1 pathway. Funding: National Institute for Health Research (NIHR) Oxford Biomedical Research Centre (BRC).